Implementasi Foot Massage Untuk Menurunkan Kelelahan pada Pasien Gagal Ginjal Kronik di Rumah Sakit Vita Insani Pematangsiantar - Siti Nurzannah; Wulan Sari Purba (Universitas Pahlawan Tuanku Tambusai, 2024)
Chronic renal failure (CKD) is the failure of the kidney function to maintain metabolic fluid and electrolyte balance due to progressive damage to the kidney structure due to the accumulation of metabolic waste in the blood. This study aims to describe the application of foot massage in reducing fatigue in patients with chronic kidney failure. The method used in this research is descriptive with a case study approach. Samples were taken from 2 respondents who experienced chronic kidney failure and were being treated at the Vita Insani Pematangsiantar Hospital using techniques, interviews, and purposive sampling. Data was collected using observation techniques, interviews, physical examination, supporting examinations, and documentation. The research showed that clients 1 and 2 complained that their legs felt weak, lacked energy, and their bodies felt weak. The nursing problem is fatigue. The intervention and implementation specified for clients 1 and 2 was doing a foot massage. During the three days of treatment, the client's fatigue decreased. Application of foot massage can reduce fatigue in patients with chronic kidney failure. It is hoped that Foot Massage can be used as an independent nursing intervention to reduce fatigue in patients with chronic kidney failure.